GANGGUAN KOGNITIF PADA LANJUT USIA DENGAN EXCESSIVE DAYTIME SLEEPINESS - Nurul Komari*, Manfaluthy Hakim*, Diatri Nari Lastri*, Joedo Prihartono** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION SLEEP DISORDER WAS ONE OF MAJOR PROBLEMS IN ELDERLY BUT HAD LESS ATTENTION EXCESSIVE DAYTIME SLEEPINESS EDS WAS MAIN SYMPTOM OF SLEEP DISORDER THAT COULD CAUSE COGNITIVE IMPAIRMENT OF THE ELDERLY NOTED WHEN SOMEONE FALLS ASLEEP IN AN INAPPROPRIATE TIME AND PLACE AND LOWERING THEIR QUALITY OF LIFE THE PURPOSE OF THIS STUDY WAS TO KNOW THE IMPACT OF EDS TO COGNITIVE FUNCTION IN ELDERLY